2010
DOI: 10.1111/j.1442-2050.2009.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of endoscopy in diagnosis and management of patients with dysphagia in an African setting

Abstract: The objectives of this study were to define the utility of esophagogastroduodenoscopy in the diagnosis and management of patients presenting with dysphagia and to determine the relative incidence of the various causes of dysphagia in Sudan. This is a prospective, cross-sectional, descriptive, hospital-based study carried out at the endoscopy unit of Soba University Hospital, Khartoum, Sudan. All patients complaining of dysphagia underwent upper gastrointestinal endoscopy with therapeutic intervention when nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
8
2
Order By: Relevance
“…Many risk factors, including EBV, may be involved in the development of esophageal cancer. Although there is no a clear-cut association between EBV infection and EC, but there is evidence that EBV infection may contribute to esophageal cancer in certain high-risk populations [12]. However, in the present study we found a prevalence of 21.5% of infection of EBV among Sudanese patients with EC.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Many risk factors, including EBV, may be involved in the development of esophageal cancer. Although there is no a clear-cut association between EBV infection and EC, but there is evidence that EBV infection may contribute to esophageal cancer in certain high-risk populations [12]. However, in the present study we found a prevalence of 21.5% of infection of EBV among Sudanese patients with EC.…”
Section: Discussioncontrasting
confidence: 55%
“…Relatively higher prevalence rates were previously reported in some studies. In study from German investigated 37 patients with esophageal carcinoma (Esophageal squamous cell carcinomas (n=23) and adenocarcinoma (n=14)) for the presence of human EBV DNA, EBV was detected in 35% of squamous cell carcinomas and 36% of adenocarcinoma [12]. Nevertheless in the present study EBV positive was found in 27.3% of the cases of the adenocarcinoma and 21% of the cases of SCC.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Dysphagia often is characteristic of malignancy [1,10], whereas epigastric or abdominal pain often are associated with normal findings [11,12]. However, indications and endoscopic diagnoses vary widely within sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%